Knowledge, Attitude and Practice on Electronic Cigarette and their Associated Factors among Undergraduate Students in a Public University - Jaafar, Hafiz; Mohd Razi, Nuurain Amirah; T. Mohd, Tengku Amatullah Madeehah; Mohamad Noor , Nadeeya ‘Ayn Umaisara; Ramli, Shalinawati; A. Rahman , Zairina; Abu Baharin , Mohamed Fakhri; Mohd Rani , Mohd Dzulkhairi; Mohamed Salleh , Nooriah (IIUM Medical Journal Malaysia, 2021)
Introduction: Smoking tobacco has been a longstanding issue worldwide, but the trend of smoking electronic cigarette (e-cigarette) is now on the rise. Many people have the view that smoking e-cigarette is safer and less harmful, and this is worrying. Adolescents and young adults are easily influenced by advertisements on e-cigarette. Thus, this study was conducted to determine the knowledge, attitude, and practice on e-cigarette among university students. Materials and methods: A cross-sectional study using self-administered questionnaire among 484 university students was carried out in a public university in Negeri Sembilan, Malaysia. Results: Respondents were 19 to 25 years old undergraduates, with the majority being female. In terms of smoking status, 32 (6.6%) of them were smokers, with only nine have ever tried e-cigarette, and only one being a regular user. Bivariate analysis showed knowledge, attitude and practices score on e-cigarette were correlated. Statistically significant associations were found between knowledge score and gender (p<0.001), while attitude and practice scores were associated with gender (p<0.001), household income (p = 0.013 and p = 0.001 respectively), as well as smoking status (p<0.001). Multivariate analysis revealed that being female and being a non-smoker were associated with higher attitude and practice scores. Conclusion: In conclusion, the awareness on e-cigarette needs to be improved among young adults and a more holistic intervention strategy should be implemented to prevent the rise of e-cigarette smoking.